Can vocal conditioning trigger a semiotic ratchet in marmosets? - Turesson, Hjalmar K.; Ribeiro, Sidarta (Frontiers in Psychology, 2015)
The complexity of human communication has often been taken as evidence that our language reflects a true evolutionary leap, bearing little resemblance to any other animal communication system. The putative uniqueness of the human language poses serious evolutionary and ethological challenges to a rational explanation of human communication. Here we review ethological, anatomical, molecular and computational results across several species to set boundaries for these challenges. Results from animal behavior, cognitive psychology, neurobiology, and semiotics indicate that human language shares multiple features with other primate communication systems, such as specialized brain circuits for sensorimotor processing, the capability for indexical (pointing) and symbolic (referential) signaling, the importance of shared intentionality for associative learning, affective conditioning and parental scaffolding of vocal production. The most substantial differences lie in the higher human capacity for symbolic compositionality, fast vertical transmission of new symbols across generations, and irreversible accumulation of novel adaptive behaviors (cultural ratchet). We hypothesize that increasingly-complex vocal conditioning of an appropriate animal model may be sufficient to trigger a semiotic ratchet, evidenced by progressive sign complexification, as spontaneous contact calls become indexes, then symbols and finally arguments (strings of symbols). To test this hypothesis, we outline a series of conditioning experiments in the common marmoset (Callithrix jacchus). The experiments are designed to probe the limits of vocal communication in a prosocial, highly vocal primate 35 million years far from the human lineage, so as to shed light on the mechanisms of semiotic complexification and cultural transmission, and serve as a naturalistic behavioral setting for the investigation of language disorders.